2021
DOI: 10.3390/biology10080728
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Worsening One Month after Transarterial Radioembolization Predicts Progressive Disease in Patients with Advanced Hepatocellular Carcinoma

Abstract: (1) Background: To demonstrate correlation between skeletal muscle depletion measured before and after one month of TARE treatment and its induced local response rate. (2) Material and methods: For this retrospective, single center study, we evaluated 86 patients with HCC treated with TARE. Sarcopenia status was measured using the psoas muscle index (PMI). The PMI was calculated according to the formula: PMI [mm/m2]: [(minor diameter of left psoas + major diameter of left psoas + minor diameter of right psoas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…A total of 57 studies involving 9790 HCC patients were included in the meta-analysis. The studies were conducted in different regions, with 41 studies 3 , 24 , 26 28 , 32 37 , 39 41 , 43 51 , 54 60 , 62 , 63 , 66 69 , 71 , 73 76 (Japan provided the largest volume of studies, followed by the South Korea) from Asia, and 16 studies 21 23 , 25 , 29 31 , 38 , 42 , 52 , 53 , 61 , 64 , 65 , 70 , 72 conducted in non-Asia regions. The enrolled patients covered all stages of HCC (from BCLC stage 0/A to BCLC stage D) and the corresponding treatments (RFA, hepatectomy, LDLT, TACE, TARE, radiotherapy, sorafenib, lenvatinib, and ICIs).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 57 studies involving 9790 HCC patients were included in the meta-analysis. The studies were conducted in different regions, with 41 studies 3 , 24 , 26 28 , 32 37 , 39 41 , 43 51 , 54 60 , 62 , 63 , 66 69 , 71 , 73 76 (Japan provided the largest volume of studies, followed by the South Korea) from Asia, and 16 studies 21 23 , 25 , 29 31 , 38 , 42 , 52 , 53 , 61 , 64 , 65 , 70 , 72 conducted in non-Asia regions. The enrolled patients covered all stages of HCC (from BCLC stage 0/A to BCLC stage D) and the corresponding treatments (RFA, hepatectomy, LDLT, TACE, TARE, radiotherapy, sorafenib, lenvatinib, and ICIs).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, as the cut-off value increased, the prevalence of sarcopenia increased. The prevalence of sarcopenia ranged from 11.1% to 78.3% in 52 studies available 21 , 22 , 24 34 , 36 – 52 , 54 70 , 72 76 for the prevalence data, and the pooled prevalence was 41.7% (95% CI 36.2–47.2%) (Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous literatures, the efficacy of TKI therapy, liver transplantation, intra-arterial chemoembolization, and transarterial radioembolization has been linked to muscle status in patients with HCC. 13 , 14 , 23 , 27 29 A recent study suggested that sarcopenia may not be associated with an increased risk in patients with HCC receiving PD-1 inhibitors. 15 Given the small sample size of the mentioned study and the lack of a report on whether the baseline information of the two groups was balanced, further investigation is required to validate these findings.…”
Section: Discussionmentioning
confidence: 99%